2009
DOI: 10.1115/1.3120410
|View full text |Cite
|
Sign up to set email alerts
|

The Wavelike Plastic Deformation of Single Crystal Copper

Abstract: The purpose of this work is to explore nonuniform plastic flow at small length- and time-scales. Pure single crystal copper tensile specimens were pulled along the [6¯ 5 6] crystal axis at three nominal strain-rates: 0.01%/s, 0.04%/s, and 0.10%/s. Simultaneously, the surface deformation was monitored with in situ digital image correlation over a length-scale of ∼100 μm and a time-scale of 0.07–0.2 s. Sequential digital image correlation strain-rate fields show compelling evidence of a wavelike plastic deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
2
13
0
2
Order By: Relevance
“…Quantum models were applied to explain the tunnel effect observed by dislocation motion [27,28]. On the other hand, recent theoretical and experimental studies indicate that the plastic flow involves wave processes [1][2][3][4][5]7,29,30]. The above findings justify the use of quantum concepts to address plastic flow development in solids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum models were applied to explain the tunnel effect observed by dislocation motion [27,28]. On the other hand, recent theoretical and experimental studies indicate that the plastic flow involves wave processes [1][2][3][4][5]7,29,30]. The above findings justify the use of quantum concepts to address plastic flow development in solids.…”
Section: Discussionmentioning
confidence: 99%
“…Recently strong experimental evidences for the above viewpoint were presented independently by several workers [3][4][5]. In order to visualize the localization patterns observed by mechanical testing, a technique of double-exposure speckle-photography was developed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Для объяснения водородных эффектов развито много микроскопических моделей, например [17], базирующихся на теории дислокаций. Однако такие подходы представляются недоста-точными, поскольку не учитывают того обстоятельства, что пластическая деформация твер-дых тел развивается локализовано на всем протяжении процесса течения [10,11,[18][19][20]. Особенно эффектно этот процесс проявляется на макромасштабном уровне, когда формиру-ющиеся локализационные паттерны оказываются однозначно связанными с законами де-формационного упрочнения     , действующими на соответствующей стадии процесса.…”
Section: заключениеunclassified
“…However, speculation continues concerning elastic waves, which occur in an elastically deforming solid and plastic waves, which are distinct from the former in the sense that they are associated with the propagation of plastic flow fronts in the deforming material. During the recent decades numerous investigations have addressed the generation of the above two classes of waves in a deforming solid [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The physical properties of these waves and the conditions favoring their generation have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the experimental studies of plastic flow in metals and alloys [1][2][3][4][5] have unambiguously demonstrated its tendency towards localization behavior from yield point to failure. Typical localization patterns observed by mechanical testing using a technique of double-exposure speckle-photography [6] are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%